2021
DOI: 10.1097/brs.0000000000004251
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Evolution of Sagittal Parameters Over Time Does Not Differ by Upper Instrumented Vertebra

Abstract: Study Design. Retrospective cohort study.Objectives. The aim of this study was to examine sagittal alignment over time in adult spinal deformity (ASD) and to understand whether these changes vary by choice of upper instrumented vertebra (UIV). Summary of Background Data. Recent ASD literature has focused on specific alignment goals. Less is known about how sagittal parameters evolve over time after surgical correction and whether these changes differ by choice of UIV. Methods. This was a retrospective review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Nevertheless, literature regarding the regression of postoperative CIB was limited. Recent articles [26][27][28] reported a progressive loss of sagittal balance after degenerative scoliosis has been corrected, indicating that most elderly patients have compensatory ability and alteration of postoperative sagittal balance. Thus, when monitoring the postoperative CB, particularly for patients with immediate balance after surgery, it is important to pay attention to the dynamic change process during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, literature regarding the regression of postoperative CIB was limited. Recent articles [26][27][28] reported a progressive loss of sagittal balance after degenerative scoliosis has been corrected, indicating that most elderly patients have compensatory ability and alteration of postoperative sagittal balance. Thus, when monitoring the postoperative CB, particularly for patients with immediate balance after surgery, it is important to pay attention to the dynamic change process during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age at the time of the surgery was 63. 5 9.6 years, 80.3% were female, the mean Body Mass Index was 27.9 kg/m 2 5.8, the median Charlson Comorbidity Index was 2 [interquartile range (IQR: 1-3)] and 56.9% had a history of previous spine surgery (Table 1). Preoperative PROs demonstrated severe disability with a mean Oswestry Disability Index of 45.9 15.9, mean Short Form 36 Physical Component Score of 30.2 8.9, and mean total SRS score of 2.71 0.61 (Table 1).…”
Section: Study Samplementioning
confidence: 99%
“…The relationship between sagittal alignment, patient-reported outcomes (PROs), and mechanical complications within adult spinal deformity (ASD) is well known 1–4 . However, several authors have shown that many patients experience worsening sagittal alignment after their initial correction 5 . Given the relationship between alignment and PROs, it would follow that the long-term maintenance of the correction is critical to ensuring satisfactory long-term outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations